Shadow Puppets Performance of Yogyakarta through its Visual Language - Ika Ismurdyahwati (Journal of Visual Art and Design, 2013)
The shadow puppet performance conveys its story to the viewers through its visual language. The aim of this research is to reveal the visual language of the gesture effects in the shadow images of the shadow puppet performance of Yogyakarta. Visual language stands for the representative images that are similar to the original objects and the way to draw it. In the case of shadow puppet performance of Yogyakarta, Central Java, Indonesia, the way to draw the images correlated to the space-time-plane system of drawing. The space-time-plane system has the characteristic to have multiple angles, distances and moments. The results of this research were each movements of the main puppet character determine it own body language.